Recent Advances in Difluoromethylation Reaction - Lu, Yang; Liu, Chao; Chen, Qing-Yun (Current Organic Chemistry, 2015)
Impressive progress has been achieved during the past decade in the incorporation of various fluroinecontaining groups, especially lightly fluorinated groups, into organic compounds. Among them, the introduction of difluoromethyl group into a compound commonly brings about many special and important effects. Two major strategies have been developed: (1) direct transfer of a CF2H group into target molecules (direct difluoromethylation); (2) the introduction of a functionlized moiety into organic substrates followed by subsequent transformation of the functional group into hydrogen or fluorine atoms (stepwise difluoromethylation). This mini review summarizes the recent developments in the selective direct and stepwise difluoromethyaltion methods during the past six years.
Keywords: difluoromethyl synthons